SOCIO-ECONOMIC IMPACT ON TEXT PROCESSING - Obiukwu, Elizabeth Nkechi; Ogwudile, Christian E. C (ESUT JOURNAL OF SOCIAL SCIENCES, 2024)
High level academic attainment in the University mainly depends on the existing pre-entry attributes including the mastery of some fundamental language skills such as text processing. Text processing is a complex and meaningful socio-cultural, cognitive and linguistic process in which processors simultaneously use their socio-linguistic context to construct meaning with text. An in depth study of English as a second language (ESL) text processing must take into consideration socio-economic background variables that impact on students’ academic achievement in the university. This study looked at text processing proficiency from the sociology of language viewpoint. It started by describing the key concepts and sub-concepts of Sociology of Language and Text Processing. Five research questions (hypothesis) were stated among them were to ascertain to what extent socio-economic background (SEB) of first year students in the University in Enugu State affect their text processing, to identify the SEB variables that affect their text processing and which of the variables exerts the greatest influence on text processing of these students. The research adopted survey design which is quantitative based. The population for this research consists of all the first year students in the four major universities in Enugu State. The sample size for the study comprised four hundred and ninety eight (498) students from the major universities in the study area. Primary data for the study were collected, using text passages selected from familiar and unfamiliar social contexts, using multiple-choice questions. The data were analyzed using simple percentage and Z-test analysis. The work revealed that the level of parents’ education, income, home environment, language of the home, social class and attitudes were prevailing socio-economic variables that exerted very high influence on the first year students’ text processing in the selected universities in Enugu State. The study concluded that economic and social background of parents has important influences on students’ text processing.